2018
DOI: 10.1007/s00268-018-4544-7
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Parathyroid Hormone Assay Remains Predictive of Cure in Renal Impairment in Patients with Single Parathyroid Adenomas

Abstract: Although the reduction in ioPTH after successful parathyroidectomy is lower in severe CKD, the Miami criterion remains predictive of cure. Differences in absolute levels of PTH and tumour weight suggest that renal HPT may be a confounding factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…In 2018, Egan et al 24 evaluated the influence of renal function deterioration on the kinetics of ioPTH decrease in a cohort of patients with 1HPT of uniglandular etiology and undergoing successful PTx. The authors reported significant differences only with severe renal function impairment, stage 4 and 5 of chronic kidney disease (CKD), primarily at 5 minutes after PTx, but that the kinetics started to equalize after 10 minutes, despite more slowly in renal patients.…”
Section: Discussionmentioning
confidence: 99%
“…In 2018, Egan et al 24 evaluated the influence of renal function deterioration on the kinetics of ioPTH decrease in a cohort of patients with 1HPT of uniglandular etiology and undergoing successful PTx. The authors reported significant differences only with severe renal function impairment, stage 4 and 5 of chronic kidney disease (CKD), primarily at 5 minutes after PTx, but that the kinetics started to equalize after 10 minutes, despite more slowly in renal patients.…”
Section: Discussionmentioning
confidence: 99%
“…The main target organs of PTH action are bone and kidney, which mobilize bone calcium into the blood and promote the reabsorption of calcium ions and the excretion of phosphate in renal tubules, so as to increase the level of blood calcium and decrease the level of blood phosphorus. In addition, PTH also indirectly promotes the intestinal absorption of calcium ions [13,14] .When tumor surgery, illness, or other causes PTH secretion decline, will cause the body hypocalcemia, and low blood calcium level will cause different clinical symptoms, light person such as oral and extremities numbness, cramps nervous system performance, the person that weigh can have syncope, arrhythmia, such as system performance, there are even suffocation crisis due to laryngospasm patient safety [15] . The role of PTH is so important, and in the thyroid surgery, parathyroid anatomical morphology and adipose tissue, lymphoid tissue is very close to the naked eye to distinguish the difficulty of a relatively large, and many patients parathyroid smaller or some position variation is larger, more increased injured or accidentally cut the risk of parathyroid gland, so parathyroid recognition and protection is of great urgency.…”
Section: Discussionmentioning
confidence: 99%